The The Cipp Analysis of PAI Development Program for Mualaf in MCI Palangka Raya - Irnadia Andriani; Zainap Hartati; Surawan Surawan (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2021)
This research is based on researchers' observations that the development of mualaf in Palangka Raya does not receive serious attention. The purpose of this research was to describe the context, input, process, and products (results) of the PAI development program for mualaf at MCI Palangka Raya. This research is evaluation research using mixed methods and the CIPP model. The results showed that the CIPP PAI development program analysis for mualaf at MCI Palangka Raya was: 1) Context, namely unfulfilled needs including institutional support, family support, and development materials. Meanwhile, the material on akidah and sharia is material that has not been achieved and material for worship and morals that is easily attained. 2) Input, namely the presenters are by their expertise, enthusiasm for mualaf to participating in development is low, the response of mualaf is excellent, and the condition of the development facilities and infrastructure is not adequate. 3) Process, namely the mismatch of the implementation schedule and the specified material. In addition, the utilization of facilities and infrastructure has not been maximized. The program implementation process still encountered several obstacles. 4) Product (result), namely the achievement of program objectives, are classified as high and the development program has a religious impact on qualify. Based on the results of this analysis, the PAI development program for mualaf at MCI Palangka Raya was continued with several improvements